PENGARUH PROMOSI DAN HARGA TERHADAP MINATBELI PRODUK SUPERMARKET SYARIAH PADA GENERASI Z DENGAN MODERASI RELIGIUSITAS - Felysia Suganda Putri; Yudi Sutarso (Qolamuna : Jurnal Studi Islam, 2024)
Sakinah Surabaya Supermarket is a company engaged in the retail sector. The company uses sharia principles in carrying out its operations. To overcome the increasingly fierce competition in the retail industry, a company must pay attention to promotions and prices to attract consumers to buy. This research will also confirm the role of the moderating variable religiosity in consumers in relation to price and promotion. This study involved a sharia retail company (Sakinah supermarket Surabaya), and 153 Sakinah supermarket consumers who were selected using a purposive sampling technique. Data analysis was performed with Structural Equation  Model-Partial Least Square (PLS SEM). From the results of the research conducted, the main findings of this study are the effect of promotion on purchase intention, but not on price perceptions. Another important finding is the role of Islamic religiosity on purchase intention, where consumers with high religiosity will be more sensitive to this influence. The main finding of this study is the effect of promotion on purchase intention, but not on price perception. Another important finding is the role of Islamic religiosity on purchase intention, where consumers with high religiosity will be more sensitive to this influence. For practitioners, this research provides guidance on price and promotion management to increase consumer buying interest. In addition, practitioners can also see differences in religiosity in terms of price, promotion and the implications for consumer buying interest. Keywords : Price, Purchase Intention, Promotion, Religiosity, Sharia Supermarket